Job satisfaction in professors from a public university medical school - Cruz Boullosa, Víctor (2019)
Introduction. Job satisfaction is important for the quality of service achievement in the organization. Objective. To determine job satisfaction in professors, who were working on Academic Department of Morphological Sciences of Facultad de Medicina in Universidad Nacional Mayor de San Marcos, during 2014. Methods. A transversal study. The Descriptive Work Index Questionnaire (JDI) was applied in 21 professors, to evaluate general job satisfaction and five specific dimensions: Current work, remuneration, opportunities, colleagues and supervision. Results. 14 professors of Anatomy and 7 professors of histology and embryology were interviewed. 71% of people were men, with an average age of 62,3 years, the majority with a service time between 30 to 39 years (61%). The dimension with the highest average score was satisfaction with current work (35,1 points); while the dimension with greater dissatisfaction is the remuneration (17,8 points). Conclusion. Despite the age and time of service, morphology professors show satisfaction with current work, independently of remuneration and other variables.